- 1-800-665-6601
- [email protected]

Step 1:- The given equation of a line is

x + 3y – 3= 0

Step 2: first we can shift the constant and x terms to the right side of the equality

3y = - x + 3

Step 3: Next we can divide the equation by 3, then we get

Y= (

3

Step 4: we can compare the above equation with

y = mx + b

Step 5: then we have

3

Step 1:- The given equation of a line is

-6x + 2y + 3= 0

Step 2: first we can shift the constant and x terms to the right side of the equality

2y = 6x – 3

Step 3: Next we can divide the equation by 2, then we have

y = 3 x – (

2

Step 4: we can compare the above equation with

y = mx + b

Step 5: then we have